Trend of media reporting on the issues of liberal Islam and religious pluralism - Latifah Abdul Majid (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2020)
This paper aims to analyze the latest trend of the official print media on the Liberal and Religious Pluralism schools of thought. The present study follows a contextual and analytical methodology to identify the practices of freedom of expression by the mass media in the issue of Liberal Islam and Religious Pluralism. This paper demonstrated that the mass media needs to be prudent in exercising freedom of expression, especially in reporting matters of communalism/racism and religion. Even so, this liberty may disrupt the harmony of a plural society if there is no control or guideline, particularly in issues relating to Islam. In addition, it may also cause the Muslim society to be confused or misunderstand and deny the views of the authorities on these thoughts. This paper discovers that Liberal Islam and Religious Pluralism are schools of thought which require openness of ijtihad (independent reasoning) beyond the limits or restrictions in Islamic Shariah. It is increasingly spreading unnoticed by the society. One of the mediums which play a big role in spreading these thoughts is the mass media, particularly the mainstream print media and internet surfing.